Two new genera of Neotropical Dasymutillini (Hymenoptera, Mutillidae, Sphaeropthalminae): Goncharovtilla gen. nov. from Brazil and Dasyphuta gen. nov. from Panama - Williams, Kevin A.; Cambra, Roberto. A.; Bartholomay, Pedro R.; Lopez, Vinicius M.; Brothers, Denis J.; Martins, Herbeson O. J.; Ferreira, Vinina S.; Koroiva, Ricardo; Guillermo-Ferreira, Rhainer (Zootaxa, 2024)
Two new monotypic genera are described within the tribe Dasymutillini: Goncharovtilla Williams, Bartholomay & Lopez, gen. nov. (type species: G. oblomovi Williams, Bartholomay & Lopez, sp. nov.) and Dasyphuta Cambra, Williams & Brothers, gen. nov. (type species: D. gorgupea Cambra, Williams & Brothers, sp. nov.). Both genera are known from both sexes. A key to the genera of Dasymutillini from the New World is provided. With these new genera the tribe Dasymutillini now contains 13 genera.